The sense and information conveyed in the translation of the verbal-visual texts - Tomaszkiewicz, Teresa (Studia Romanica Posnaniensia, 2007)
This article focusses on the search for a solution to problems of translation of texts of a verbal-visual character. Despite appearance various images occurring in these texts are not automatically understood by a foreign recipient since they undergo a certain codification, characteristic of every culture individually. In the meantime the sense of these verbal-visual tramsmissions is a result of various relations into which enter with each other both semiotic elements (parallel, supplementing and interpretative meaning, equivalence and contradiction). The author tries to answer the question about the way in which the translator of this type of texts may render their sense and transmit information contained in them for the use of a foreign recipient.